Comparative Transcriptomics and RNA-Seq-Based Bulked Segregant Analysis Reveals Genomic Basis Underlying Cronartium ribicola vcr2 Virulence - Liu, Jun-Jun; Sniezko, Richard A.; Zamany, Arezoo; Williams, Holly; Omendja, Kangakola; Kegley, Angelia; Savin, Douglas P. (Frontiers in Microbiology, 2021)
Breeding programs of five-needle pines have documented both major gene resistance (MGR) and quantitative disease resistance (QDR) to Cronartium ribicola (Cri), a non-native, invasive fungal pathogen causing white pine blister rust (WPBR). WPBR is one of the most deadly forest diseases in North America. However, Cri virulent pathotypes have evolved and can successfully infect and kill trees carrying resistance (R) genes, including vcr2 that overcomes MGR conferred by thewestern white pine (WWP, Pinus monticola) R gene (Cr2). In the absence of a reference genome, the present study generated a vcr2 reference transcriptome, consisting of about 20,000 transcripts with 1014 being predicted to encode secreted proteins (SPs). Comparative profiling of transcriptomes and secretomes revealed vcr2 was significantly enriched for several gene ontology (GO) terms relating to oxidation-reduction processes and detoxification, suggesting that multiple molecular mechanisms contribute to pathogenicity of the vcr2 pathotype for its overcoming Cr2. RNA-seq-based bulked segregant analysis (BSR-Seq) revealed genome-wide DNA variations, including about 65,617 single nucleotide polymorphism (SNP) loci in 7,749 polymorphic genes shared by vcr2 and avirulent (Avcr2) pathotypes. An examination of the distribution of minor allele frequency (MAF) uncovered a high level of genomic divergence between vcr2 and Avcr2 pathotypes. By integration of extreme-phenotypic genome-wide association (XP-GWAS) analysis and allele frequency directional difference (AFDD) mapping, we identified 82 vcr2-associated SNPs within 48 genes, involved in fungal virulence and other molecular functions, including five SPs which were top candidate effectors with putative activities of reticuline oxidase, proteins with CFEM domain or ferritin-like domain, polysaccharide lyase, and unknown function. Candidate effectors and vcr2-associated genes provide valuable resources for further deciphering molecular mechanisms of virulence and pathogenicity by functional analysis and the subsequent development of diagnostic tools for monitoring the virulence landscape in the WPBR pathosystems.